(3GdHOQ GdWGdY ef GdVhA GddGeY dCgd GdbQf GdJGSYs - (3CHh GdNjQ TgGH GdOjf CMeO Hf eMeO Hf eMeO Hf YHO GdSdGe Hf ehSi Gdefhai GdbGgQjs; (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s
(3ChdgG (B:s
,(3HYO abO hbYJ Mjf eLGhQJi HecI GdeTQag Sfg (B905 (3Ydi cJGH GdVhD GddGeY s
(3BNQgG (B:s
(3hefge GdeDda Yed ai GdehdO LRGA dUjakG ceG GTGQ Edjg ai YOO eDdaGJg (B,(3gPG BNQ eG jSQ s
(3HChdgG agQSJ HCSeGA GdeJQLejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B150s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B44 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCMeOjI HJhfS (B(5036) s
Keywords: (3GdJGQjNs